Estrategia didáctica para la enseñanza de los hechos históricos ocurridos durante la dictadura del General Gustavo Rojas Pinilla (2021)
The design of this teaching material aims to identify the causes, consequences and political characteristics that were carried out in the framework of the military dictatorship of General Gustavo Rojas Pinilla, for this the relationship between what is suggested by the 4 documents is analyzed officials proposed by the Ministry of National Education for the teaching of history, with what the students actually learn in the classroom. Since after the application of a diagnostic test in the tenth grade students of the Los Andes Technological Institute, it was reflected that their knowledge regarding national history, particularly the events that occurred during the military dictatorship of General Gustavo Rojas Pinilla, are very diffuse. The evidence of this problem led us to think of a relevant didactic tool for the students who are today in the classroom who are also digital natives due to their proximity from an early age with electronic devices and who share the academic space with digital immigrants, that is, their teachers who have a different approach to digital. With the results of the diagnostic test and what was consulted in the background, it was possible to create a route for teaching the causes, consequences and political characteristics of the military dictatorship of General Gustavo Rojas Pinilla through the design of a web page prepared for this purpose.